CONSTITUIÇÃO DO OUTRO E DO SI MESMO A PARTIR DA EINFÛNHLUNG EM EDITH STEIN - ETELVINA PIRES LOPES NUNES (Ideas y Valores)
According to Edith Stein, empathy is an experience that allows for knowledge of the other and of the "empathizing subject". The notion of "full experience" makes it possible to know the experience of the other, as well as the values underlying his/her actions. On the basis of this theory, the article seeks to respond to Levinas' proposal of total responsibility, on the one hand and to P. Ricœur, who argues in favor of a relation that, at the same time, takes into account the reflexivity of the self, on the other. Empathy allows for a personalized mode of constitution of the two subjects, which, simultaneously preserves the singularity and alterity of each.